Charakterystyki i miary jakości informacji - Gryncewicz, Wiesława (Information Quality Characteristics and Measures, 2007)
Information is of high quality if it meets users' needs. Accurate, complete and timely information is required for optimal business performance. This article defines information quality, its characteristics and measures based on infology. The authoress presents also her own proposition of information quality indicator.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 105-114